Use of Non‐Aromatic Hydrophobic α‐Amino Acids (α‐AA) and Non‐Amino Acid Derived Synthons: Comparative Studies Towards Total Syntheses of Selected Bioactive Natural Alkaloids. Issue 10 (8th March 2022) - Kumar, Amit; Bhattacherjee, Sandeep; Ganesher, Asha; Manda, Srinivas Lavanya Kumar; Banerjee, Arpita; Panda, Gautam
Abstract: Enantiomerically pure non‐aromatic α‐amino acids having hydrophobic side chains (Isoleucine, Valine, Leucine, Methionine and Alanine) have been acknowledged as an important chiral pool. The wide range of chemical and biological applications associated with these α‐amino acids has encouraged organic chemists to develop new synthetic methodologies for the total synthesis of bioactive molecules. In this review, the synthetic routes of 10 bioactive natural alkaloids have been covered. The present article is an attempt to discuss various synthetic approaches of therapeutically active natural alkaloids and related diversity from non‐aromatic hydrophobic α‐amino acids and non‐amino acid derived synthetic approaches to present a comparative study between the methods. The synthetic steps and the key strategies involved in the total synthesis of selected natural alkaloids have been compared based on atom economy, overall chemical yield, stereoselectivity and sustainability with cost effective manner by using inexpensive commercially available starting materials but the source of chiral pool mainly α‐amino acids to target natural alkaloids in chiral synthesis will be playing an important role. In selected cases of alkaloids synthesized from non‐amino acid route, an external chiral source of induction like metal and organometallic catalysts to generate chirality in the molecule are used. Abstract : Enantiomerically pure non‐aromatic α‐amino acids having hydrophobic side chains (Isoleucine, Valine, Leucine, Methionine and Alanine) have been acknowledged as an important chiral pool. This review is an attempt to discuss various synthetic approaches of therapeutically active natural alkaloids and related diversity from non‐aromatic hydrophobic α‐amino acids and non‐amino acid derived synthetic approaches to present a comparative study between the methods.